2015
DOI: 10.1029/2015eo040975
|View full text |Cite
|
Sign up to set email alerts
|

Sounding the Northern Seas

Abstract: A new compilation of underwater terrain provides the most up-to-date mapping of portions of the western Arctic and North Pacific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Keigwin et al (2006) assumed that the first marine waters to flood their core site in Hope Valley would have been sourced from the Bering Sea, and therefore the single radiocarbon age provides a minimum age for the Bering Land Bridge flooding. The most recent high-resolution bathymetric dataset for the Chukchi Sea (ARDEM; Danielson, 2015), however, suggests that the initial flooding of Hope Valley with marine waters could instead have been sourced from the Arctic Ocean rather than the Pacific (Fig. 1).…”
Section: Minimum Age Constraints For Bs Floodingmentioning
confidence: 99%
See 3 more Smart Citations
“…Keigwin et al (2006) assumed that the first marine waters to flood their core site in Hope Valley would have been sourced from the Bering Sea, and therefore the single radiocarbon age provides a minimum age for the Bering Land Bridge flooding. The most recent high-resolution bathymetric dataset for the Chukchi Sea (ARDEM; Danielson, 2015), however, suggests that the initial flooding of Hope Valley with marine waters could instead have been sourced from the Arctic Ocean rather than the Pacific (Fig. 1).…”
Section: Minimum Age Constraints For Bs Floodingmentioning
confidence: 99%
“…Key cores from previous studies referred to in this work regarding the reopening of the BS after the LGM are shown with white dots (85-69, Elias et al, 1992Elias et al, , 1996JPC 02, Keigwin et al, 2006). The bathymetry is from the Alaska Region Digital Elevation Model (ARDEM; Danielson et al, 2015). The leg 2 cruise track of the SWERUS-C3 expedition in 2014 is shown with a brown line.…”
Section: Geophysical Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…To attempt to determine the direction from which this wavefield arrived at Barrow, we used the shallow‐water phase speed to model the refraction pattern for five different wavefronts initialized in different regions of the deeper Beaufort Sea (Figure a). The wave phase speed is set to the shallow water phase speed for simplicity, and hence is nondispersive and a function that varies only with water depth (equation ), which is taken from the nearest grid point of the ARDEM bathymetry data set [ Danielson et al , ]. The resulting synthetic wavefields are largely similar to each other (Figure b), although there are slight differences in the orientation of wavefronts over Barrow Canyon.…”
Section: Discussionmentioning
confidence: 99%